Legal Protection For Parties In Economic Transactions Through Instagram - Anita Afrelia; Lathifah Hanim (Law Development Journal, 2020)
Economic online has the function of integration of marketing, implementation of E-Commerce strategies, the main purpose of increasing the number of sales. The formulation of the problem in this thesis research are: 1) How is the validity of economic transactions through Instagram according to Act No. 19 of 2016 concerning Information and Electronic Transactions? 2) How is the legal protection for the parties in economic transactions through social media Instagram according to Act No. 19 of 2016 concerning Electronic Information and Transactions? The approach method used is Normative Juridical approach. From the results of this study, 1) The validity of economic transactions through Instagram according to Act No. 19 of 2016 concerning Information and Electronic Transactions can be declared valid and becomes the base of the implementation of a contract for both parties. 2) Legal protection for the parties in economic transactions through social media Instagram according to Act No. 19 of 2016 concerning Information and Electronic Transactions that against buyers who are injured in a sale and purchase dispute consists of litigation and non-litigation.